1 Timotius 2:11-15: Sebuah Argumentasi Paulus Bagi Kesetaraan Gender Di Dalam Kepenilikan Jemaat Lokal - Jammer Prayerson Andalangi (Predica Verbum: Jurnal Teologi dan Misi, 2021)
The debate between biblical patriarchy, complementarianism, and egalitarianism continues until this very day. One of the frequently used texts to prohibit women’s role as teachers and leaders in a local church is 1 Timothy 2:11-15. Hierarchical argumentations have failed to understand Paul’s techniques for showing emphasis through a gradual or logical sequence of words in effective sentences, as well as his reference to the creation and fall story. This research investigates the text in a comparative study with Genesis 1-3. This research uses a grammatical-historical hermeneutic method that examines Paul’s logical development of argument, situations behind the statements, and different subgenres used in the letter. This research finds that Paul’s techniques for showing emphasis through words of gradual sequence and allusion to Genesis 1-3 are a defense for an equal imago Dei of man and woman and a valid basis for equal authority value of the two in church leadership.